Optimization of the production of extruded maca flour through process automation in an agro-industrial company - Mandujano Palacios, Jean Piero (2025)
The Indecopi's Directorate of Distinctive Signs (DSD), highlights the quality of Peruvianmaca, grown in the Andes in red, black and yellow varieties. According to the Ministry of Agrarian Development and Irrigation(MIDAGRI), with 3,201 hectares of cultivation, 18,359.92 tons are produced, valued at 11.96 million soles, which makes it anattractive option for companies.This study focuses on optimizing the production of extruded tricolor maca flour in “SuperNaturals Food SAC”. A Process Operations Diagram (DOP) was developed, providing a graphical representation of each operation,which facilitates the understanding of the production sequence. To improve efficiency, tools such as the Ishikawa Diagram, toanalyze root causes of problems, and Value Stream Mapping (VSM), comparing the current state with an ideal one, were employed.This allowed the identification of problems such as lack of monitoring in extrusion and inadequate moisture control. A machine witha temperature sensor was introduced, achieving a gelatinization of more than 94%. A cooling tunnel with humidity sensors and anautomated packaging machine were also installed. In addition, conveyors were implemented for a continuous flow. Theimprovements reduced the loss from 8 to 0% and doubled the production capacity, reducing the manufacturing time of 500 kg offlour from 14 to 7 days, increasing annual income by S/8,789.28. The controls ensure consistent high-quality production, improvingthe company's competitiveness.